62 Racial differences in self-efficacy and patient-provider interactions among patients with systemic lupus erythematosus. (April 2019) - Sun, Kai; Eudy, Amanda M; Rogers, Jennifer L; Criscione-Schreiber, Lisa G; Doss, Jayanth; Sadun, Rebecca E; Clowse, Megan EB
Abstract : Background: Significant racial disparities exist in the prevalence and outcomes of systemic lupus erythematosus (SLE). Few studies have examined modifiable factors intrinsic to a patient encounter that may contribute to such disparities. We aimed to explore potential areas for intervention to reduce racial disparities with a focus on patient self-efficacy and the quality of patient-provider interactions. Methods: Cross-sectional data were collected from consecutive SLE patients actively treated and followed at a tertiary lupus clinic. Patient-provider interaction was measured using the Interpersonal Processes of Care survey (IPC-29), which has 7 domains on a 5-point Likert scale including Hurried communication, Elicited concerns, Explained results, Patient-centered decision making, Compassionate respectful, Discrimination, and Disrespectful office staff. General self-efficacy, self-efficacy for managing medications and treatments, and patient-reported health status were measured using Patient-Reported Outcomes Measurement Information System (PROMIS) short forms. Additional demographic and clinical information were gathered by survey and chart review. SLE Disease Activity Index (SLEDAI), Systemic Lupus International Collaborating Clinics (SLICC) Damage scores, and Medication Regimen Complexity Index were calculated. Bivariate analyses compared patient characteristics of Caucasians and non-Caucasians. Results: 84 enrolled (37% Caucasians, 59% African American, 1% Native American, and 4% Hispanic). Non-Caucasians compared to Caucasians are younger, more likely to be single/unmarried, on disability, and less likely to have college education. Non-Caucasians tend to report less fatigue, better social health, carry a more recent SLE diagnosis but take a more complex rheumatic medication regimen, have higher SLEDAI, lower fibromyalgia symptom severity, and a trend for higher damage scores (table 1 ). In terms of modifiable factors intrinsic to the patient encounter, there were no significant differences in patient-provider interactions except that non-Caucasians rated providers to have more Hurried communication. Non-Caucasians also had a trend for lower general self-efficacy. Conclusions: Non-Caucasians come from more disadvantaged sociodemographic backgrounds and have worse SLE disease outcomes. Overall, scores for patient-rated interactions with physicians in this selective sample were better than in other studies. However, non-Caucasians reported more Hurried communication with their providers and lower general self-efficacy. These may be modifiable factors within a patient encounter to reduce healthcare disparities in SLE. Whether quality of patient-provider communication and patient self-efficacy predict higher disease activity and damage scores longitudinally should be investigated. Funding Source(s): 5U54MD012530-02